A new species of Pareas (Serpentes: Colubridae: Pareatinae) from the Gaoligong Mountains, southwestern China - Guo, Keji; Deng, Xuejia (Zootaxa, 2009)
A new species of Pareas Wagler, 1830 (Serpentes: Colubridae: Pareatinae) is described from Gaoligong Mountains, Yunnan province, southwestern China. The new species is distinguished from congeners in the following combination of traits: preoculars 1/1; subocular and postocular fused into a single crescent-shaped scale; anterior temporals 1, posterior 2–3; 15 dorsal rows on whole body, 9 median rows feebly keeled (invisible on neck); vertebral scales slightly enlarged; ventrals 175; subcaudals 76 (excluding terminal spine), all divided; a big black oval patch on the back of head; two round black spots on each side of the face.